Runaway electron modelling in the self-consistent core European Transport Simulator. (7th June 2019) - Pokol, Gergo I.; Olasz, Soma; Erdos, Boglarka; Papp, Gergely; Aradi, Matyas; Hoppe, Mathias; Johnson, Thomas; Ferreira, Jorge; Coster, David; Peysson, Yves; Decker, Joan; Strand, Par; et al.
Abstract: Relativistic runaway electrons are a major concern in tokamaks. Although significant theoretical development had been undertaken in recent decades, we still lack a self-consistent simulator that could simultaneously capture all aspects of this phenomenon. The European framework for Integrated Modelling (EU-IM) facilitates the integration of different plasma simulation tools by providing a standard data structure for communication that enables relatively easy integration of different physics codes. A three-level modelling approach was adopted for runaway electron simulations within the EU-IM. Recently, a number of runaway electron modelling modules have been integrated into this framework. The first level of modelling ( Runaway Indicator ) is limited to the indication if runaway electron generation is possible or likely. The second level ( Runaway Fluid ) adopts an approach similar to e.g. the GO code, using analytical formulas to estimate changes in the runaway electron current density. The third level is based on the solution of the electron kinetics. One such code is LUKE that can handle the toroidicity-induced effects by solving the bounce-averaged Fokker–Planck equation. Another approach is used in NORSE, which features a fully nonlinear collision operator that makes it capable of simulating major changes in the electron distribution, for example slide-away. Both codes handle the effect of radiation on the runaway distribution. These runaway-electron modelling codes are in different stages of integration into the EU-IM infrastructure, and into the European Transport Simulator (ETS), which is a fully capable modular 1.5D core transport simulator. The ETS with Runaway Fluid was benchmarked to the GO code implementing similar physics. Coherent integration of kinetic solvers requires more effort on the coupling, especially regarding the definition of the boundary between runaway and thermal populations, and on consistent calculation of resistivity. Some of these issues are discussed.